Effect of Alkaline treatment on the characteristics of pineapple leaves fibre and PALF/PP biocomposite - Surenthiran, Gnanasekaran; Nor Ida Amalina, Ahamed Nordin; Mimi Maisarah, Mahadi @ Hamidi; Jun Haslinda, Shariffuddin (Faculty Mechanical Engineering, UMP, 2021)
Pineapple leaves fibre (PALF) is one of the natural fibre that has high potential to substitute non-renewable synthetic fibre in thermoplastic products. The PALF were alkali treated with different concentrations of NaOH. Untreated and alkali treated PALF were characterized using Thermal Gravimetric Analysis (TGA) and Scanning Electron Microscopy (SEM) to determine the thermal stability and surface morphology of the fibres respectively. Biocomposites were prepared by reinforced alkali treated and untreated PALF with polypropylene (PP) matrix. Tensile properties and water absorption analysis of PALF/PP biocomposites were studied. Biocomposite with 8 wt.% of alkali treated PALF express excellent thermal stability, with maximum degradation temperature at 270 ℃ which is a 7.17% improvement compared to untreated PALF. This biocomposite also had increased tensile strength (116 MPa) with 43% improvement compared to untreated PALF/PP (66 MPa) biocomposite and had lower water absorption at 6% compared to untreated biocomposite which at 21%. Hence, alkali treated PALF is able to improve the characteristic of PALF and increase the compatibility between fibre and polymer by reducing hemicellulose and lignin component